Formation of Legal Norms that are of a Regulatory from the Perspective of the Theory of Division/Separation of Powers - Haeruman Jayadi; Ad. Basniwati; Khairul Umam (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Since the establishment of the Constitutional Court (MK), which has the authority to review laws against the Constitution, several MK decisions have incorporated regulatory legal norms, similar to those created by the legislative branch. This has given rise to a controversy over the formation of regulatory legal norms between the legislators and the MK, the law examiner. The question is which institution has the authority to create regulatory legal norms from the perspective of the theory of separation of powers. To address this issue, the research method used is normative legal research, using both a legislative and a conceptual approach. Based on the research conducted, it can be concluded that, from the perspective of the theory of separation of powers, the authorized institution to create regulatory legal norms is the legislative branch. Based on the theory of separation of powers, the MK does not have the authority to create new regulatory norms in its decisions to replace or supplement existing norms. This is to avoid the accumulation of power, as the creation of regulatory legal norms is essentially the responsibility of the legislative branch. The creation of regulatory legal norms by the judiciary is inconsistent with the intent of the theory of separation of powers itself. Therefore, the MPR needs to limit the Constitutional Court's authority in the 1945 Constitution by amending the 1945 Constitution.